The total contribution of the direct and indirect influence of servant leadership on innovative work behavior - Rendika Vhalery; Hendro Prasetyono; Ira Pratiwi Ramdayana; Salmin Salmin; Widya Priska Anggraini (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to determine the total contribution of servant leadership variables directly or indirectly to the innovative work behavior of high school teachers. The research respondents were 158 teachers from Jakarta Capital Special Region, Bogor Regency, Bekasi City, and Bandung Regency, Indonesia. Data analysis technique using path analysis. The results showed that the total direct and indirect contribution of servant leadership variables to innovative work behavior through knowledge sharing was 97.3%. The remaining 2.7% comes from variables not examined in this study. The implications of this research can be used by school principals and education policymakers at the national and regional levels to strengthen servant leadership to create knowledge sharing in strengthening the innovative work behavior of teachers in senior high schools.